Optimising inverse planning simulated annealing (IPSA) parameters for brachytherapy planning dose calculation in oral tongue cancer patients - Osman, Siti Noraliza (Universiti Sains Malaysia, 2025)
Brachytherapy plays an essential role in the treatment of oral tongue cancer, providing a high radiation dose directly to the tumor while limiting the exposure to surrounding healthy tissues. Inverse Planning Simulated Annealing (IPSA) is an automated optimization algorithm commonly used in brachytherapy, but its performance can be influenced by parameter settings. This study aimed to compare the dosimetric outcomes between Graphical Optimization (GrO) and three different IPSA parameter sets in brachytherapy planning for oral tongue cancer. A retrospective analysis was conducted, where the dose-volume histogram (DVH) parameters, specifically GTV (D90) and D2cc for the mandible, pharyngeal constrictor muscle (PCM), and submandibular glands (SMG), were evaluated across different plans. The findings showed that GrO achieved the highest mean GTV D90 of 6.10 Gy, while IPSA 1, IPSA 2, and IPSA 3 recorded mean D90 values of 4.14 Gy, 4.68 Gy, and 5.37 Gy, respectively. A statistically significant differences were found in GTV D90 and D2cc mandible between GrO and IPSA plans. However, for the pharyngeal constrictor muscle, left and right submandibular glands, IPSA 2 and IPSA 3, there are no significance D2cc doses compared to GrO. Although IPSA optimization provided acceptable dose conformity, none of the IPSA parameter sets outperformed GrO in target coverage. IPSA 2 showed a favorable balance between target coverage and normal tissue sparing. As a limitation, this study only analyzed data from a single treatment fraction for each patient due to unavailable multi-fraction data, which may affect the overall interpretation. Future studies should consider collecting and analyzing data for multiple fractions to enhance accuracy and allow for more comprehensive evaluation of IPSA optimization performance in oral tongue cancer brachytherapy. Among the IPSA plans, IPSA 2 is identified as the optimal parameter configuration, offering the best overall balance between tumour coverage and OAR protection. IPSA 3, while achieving higher tumour dose coverage, resulted in increased doses to the OARs, particularly the right and left submandibular glands, highlighting the need for careful trade-off management between target coverage and normal tissue sparing in inverse planning.